Morphology and Hydrogen in Passivating Amorphous Silicon Layers. (August 2015) - Gerke, Sebastian; Becker, Hans-Werner; Rogalla, Detlef; Hahn, Giso; Job, Reinhart; Terheiden, Barbara
Abstract: Hydrogenated intrinsic amorphous silicon ((i)°a-Si:H) can be grown by plasma-enhanced chemical vapor deposition with a non-columnar or columnar morphology. Nuclear resonant reaction analysis and corresponding effective stopping cross section analysis indicate a dependency of hydrogen effusion on the morphology of the (i)°a-Si:H layer as well as the doping type and concentration of the c-Si wafer. The doping type of the c-Si wafer also affects the growth of the amorphous network. It is found that for moderately doped p-type c-Si a non-columnar (i)°a-Si:H layer yields a significantly better and more stable passivation already during thermal anneal and illumination, while for passivating n-type c-Si a columnar layer is recommended. Passivating lowly doped c-Si by (i)°a-Si:H is not dependent on morphology. Combining different (i)°a-Si:H morphologies to a multi-layer stack improves the quality of surface passivation. Hydrogen embedded in a well passivating but hydrogen-permeable columnar layer supports good surface passivation when covered by a non-columnar layer, featuring a fast growing layer acting as a hydrogen barrier and enhancing surface passivation quality.